2015
DOI: 10.1053/j.semvascsurg.2015.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Transitions of care and long-term surveillance after vascular surgery

Abstract: Quality care of vascular surgery patients extends to the post-operative coordination of care and the long-term surveillance, including the medical management of vascular disease. This is particularly highlighted in contemporary modern vascular surgery practice as tremendous focus is being placed on post-operative adverse events and hospital readmissions. The purpose of this review is to provide a contemporary perspective of transitions of care at discharge and long-term surveillance recommendations after vascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Furthermore, patients with delirium are more likely to be discharged to other facilities to receive further intermediate-or long-term care, increasing the health care costs significantly. 38 Finally, frailty has been strongly associated with PODE incidence even in patients undergoing vascular surgery procedures. 16,39 However, data collected from the included studies were not sufficient to calculate frailty scores according to criteria used in major frailty scales.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, patients with delirium are more likely to be discharged to other facilities to receive further intermediate-or long-term care, increasing the health care costs significantly. 38 Finally, frailty has been strongly associated with PODE incidence even in patients undergoing vascular surgery procedures. 16,39 However, data collected from the included studies were not sufficient to calculate frailty scores according to criteria used in major frailty scales.…”
Section: Discussionmentioning
confidence: 99%
“…Transitioning care from the inpatient hospital setting to either the outpatient or inpatient rehabilitation environment can be challenging, and coordination of care is highly complex. Data have demonstrated that compliance with clinic follow-up after vascular intervention is associated with improved outcomes, 9 and this is even more important after a vascular access complication because that event predicts worse outcomes compared with matched counterparts. 1,3,4,6 Moreover, patients who suffer complications after discharge typically represent within 2 weeks, 21 raising the question of appropriateness for discharge.…”
Section: Discussionmentioning
confidence: 99%
“…8 Longitudinal surveillance and evaluation in the vascular surgery population has been associated with improved outcomes. 9 In this specific population of patients who underwent emergent CFA repair after access complications, the rate of compliance with follow-up clinic visits has not been described and may significantly impact the incidence of wound complications.…”
Section: Introductionmentioning
confidence: 98%
“…[1415] It is evident that long-term determinants of readmission are becoming increasingly important, with rehospitalizations beyond the initial postoperative 30-day being both costly and mostly unplanned,[16] yet potentially preventable. [17]…”
Section: Introductionmentioning
confidence: 99%